A high-strength plastic, easy-to-process nickel-cobalt-based wrought superalloy and a preparation method thereof
Patent Information
- Application Number
- CN202511356161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-09-22
AI Technical Summary
[0007]可见,目前报道的合金在750℃的屈服强度不超过1100MPa,断后伸长率不超过10%,且合金的屈服强度和断后伸长率之间存在此消彼长的限制
[0026]本发明的高强塑性、易加工的镍钴基高温合金,以质量百分数计包括:Co 18%~25%、Cr 11%~16%、Al 2.4%~3.4%、Ti 4.5%~6.5%,W 0.8%~2%、Mo 1.6%~3.2%、Ta 0.5%~1.5%、Nb 0%~1.5%、C0.001%~0.1%、B 0.001%~0.05%、Zr0.001%~0.1%,Hf 0~0.1%,余量为Ni。本发明通过合理的元素配比,调节了γ相和γ′相中的合金元素分配,一方面使合金在保持较高γ′相体积分数的同时具有较大的加工区间,另一方面调整合金层错能以充分利用面缺陷的交互作用对合金的强化效果。二者的综合作用为发明一种兼具高强度、高塑性和易加工的镍钴基变形高温合金提供了解决途径,进而为先进装备750℃及以上温度服役用高强度高温合金提供一种新的解决方案。
Smart Images

Figure CN121380680B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature alloy technology, specifically relating to a high-strength, ductile, and easily machinable nickel-cobalt-based wrought high-temperature alloy and its preparation method. Background Technology
[0002] High-temperature alloys, with their excellent high-temperature strength, good oxidation resistance and hot corrosion resistance, are widely used in the hot-end components of aero engines and industrial gas turbines. They are irreplaceable key metallic materials for national defense and military industry and national economic development.
[0003] With the development of aero-engines and industrial gas turbines, turbine inlet temperatures are constantly increasing. Currently, the temperature resistance requirements for aero-engine turbine disk materials have reached 760℃, while in some more demanding military equipment applications, this temperature has reached 815℃. The widely used GH4169 alloy has a stable service temperature of only 650℃, and even the higher-performance U720Li alloy does not exceed 700℃. Their temperature resistance is no longer sufficient to meet the requirements, necessitating the design of new high-temperature alloys to satisfy these demands.
[0004] A foreign patent [US9945019B2] discloses a design method for nickel-cobalt-based superalloys. This method obtains TMW series alloys with high strength in the mid-temperature range by adding a certain proportion of Co-Ti alloy to U720Li. The alloy, by mass percentage, comprises: Co: 23.1%–55%, Cr: 2%–25%, Ta: 0–10%, W: 0–10%, Mo: 0–10%, Zr: 0–0.5%, Nb: 0–5%, Ti: 3%–15.0%, Al: 0.2%–7%, Re: 0–5%, V: 0–2%, Fe: 0–2%, Hf: 0–2%, Mg: 0–0.1%, C: 0–0.5%, B: 0–0.1%, with the balance being Ni.
[0005] A domestic patent technology discloses a high-temperature alloy GH4251 with low stacking fault energy [CN112981186B]. The alloy, by mass percentage, includes: C: 0.01%~0.09%, Co: 23.5%~27.5%, Cr: 11%~15%, W: 0.1%~1.8%, Al: 2.2%~2.6%, Ti: 3.5%~5.5%, Nb: 0~2%, Ta: 0~2%, Mo: 2.1%~3.5%, B: 0.0001%~0.05%, Zr: 0.0001%~0.05%, Fe: 0~2.5%, Mg: 0~0.04%, with the balance being Ni.
[0006] According to reports, the two types of alloys mentioned above can withstand temperatures up to 750℃ and have excellent structural stability. Among them, the TMW nickel-cobalt-based superalloy has a yield strength of 1008MPa and an elongation after fracture of 9.5% at 750℃; the low stacking fault energy superalloy GH4251 has a yield strength of 965MPa and an elongation after fracture of 8.5% at 750℃, which is expected to meet the service requirements of hot-end components above 750℃.
[0007] It is evident that currently reported alloys at 750℃ have a yield strength not exceeding 1100 MPa and an elongation after fracture not exceeding 10%, with a trade-off between yield strength and elongation. High-strength wrought high-temperature alloys often exhibit mid-temperature brittleness, with elongation after fracture below 5%, while alloys with high elongation typically have a yield strength less than 1000 MPa. Consequently, with the development of advanced equipment, existing alloys are gradually revealing their shortcomings in application, failing to meet the increasingly demanding comprehensive performance requirements of high-temperature alloys for service at 750℃ and above. By fully considering the contradictions between the volume fraction of the γ′ phase, melting point, castability, and hot workability of the alloy during alloy design, as well as the synergistic effect of stacking faults, dislocations, and the γ′ phase on alloy strength, it is hoped that a synergistic improvement in various alloy properties can be achieved. Summary of the Invention
[0008] In order to overcome the above-mentioned problems in the prior art, the present invention provides a high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy and its preparation method, which is used to solve the above-mentioned problems in the prior art.
[0009] A high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy comprises, by mass percentage: Co 18%–25%, Cr 11%–16%, Al 2.4%–3.4%, Ti 4.5%–6.5%, W 0.8%–2%, Mo 1.6%–3.2%, Ta 0.5%–1.5%, Nb 0%–1.5%, C 0.001%–0.1%, B 0.001%–0.05%, Zr 0.001%–0.1%, and Hf. The alloy contains 0-0.1% Al, with the balance being Ni. The mass percentage ratio of Al to Ti is ≤0.6; the sum of the mass percentages of W and Mo is 3%-5%; the sum of the mass percentages of Nb and Ta is 0%-2%; the mass percentage ratio of Co to W+Mo is ≥4; the mass percentage ratio of Al to Nb+Ta is ≥2; and the volume fraction of the γ' strengthening phase in the high-temperature alloy is 40%-60%.
[0010] In addition to the aspects described above and any possible implementation, a further implementation is provided in which the high-temperature alloy comprises, by mass percentage: Co 20%–25%, Cr 12%–13.5%, Al 2.7%–3.2%, Ti 4.5%–6.5%, W 1.2%–1.8%, Mo 2%–2.6%, Ta 0%–1.5%, Nb 0%–1.5%, C 0.01%–0.05%, B 0.001%–0.04%, Zr 0.001%–0.04%, Hf 0–0.04%, with the balance being Ni.
[0011] In addition to the aspects and any possible implementations described above, a further implementation is provided in which the mass percentage of Co is 20% to 24% and the mass percentage ratio of Cr to Co is ≥0.5.
[0012] In addition to the aspects and any possible implementations described above, a further implementation is provided in which the high-temperature alloy has a yield strength of ≥1100 MPa at 750°C and an elongation after fracture of ≥8%; a creep life of ≥180 h at 760°C@480 MPa; and a creep life of ≥10 h at 1050°C. -2 s -1 When subjected to tensile strain at a certain strain rate, the elongation after fracture is above 1200%.
[0013] In addition to the aspects described above and any possible implementation, an implementation is further provided, wherein, by mass percentage, Co is 22%, Cr is 12.5%, Al is 2.9%, Ti is 5.5%, W is 1.6%, Mo is 2.4%, C is 0.02%, B is 0.02%, Zr is 0.03%, Hf is 0.03%, and the balance is Ni.
[0014] In addition to the aspects described above and any possible implementation, a further implementation is provided in which the high-temperature alloy comprises, by mass percentage: Co 21%–23%, Cr 12%–13%, Al 2.7%–3.1%, Ti 4.5%–6%, W 1.2%–1.6%, Mo 2.1%–2.6%, Ta 0%–1.2%, Nb 0%–1.2%, C 0.01%–0.04%, B 0.001%–0.03%, Zr 0.001%–0.03%, Hf 0–0.04%, with the balance being Ni.
[0015] In addition to the aspects described above and any possible implementation, an implementation is further provided in which the sum of the mass percentages of W and Mo is 3% to 5%, wherein the mass percentage of W is between 1% and 2% and the mass percentage of Mo is between 2% and 3%.
[0016] In addition to the aspects described above and any possible implementation, an implementation is further provided in which the sum of the mass percentages of Al and Ti is 7% to 9%.
[0017] This invention also provides a method for preparing a high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy, the method comprising the following steps:
[0018] S1. Add the raw materials to a vacuum induction furnace to melt alloy ingots;
[0019] S2. The alloy ingot is homogenized by first treating it at 1050℃~1150℃ for 12 hours, then treating it at 1150℃~1200℃ for 16 hours, and then air-cooling it to room temperature.
[0020] S3. The homogenized alloy is subjected to cladding extrusion at 1060℃~1090℃, and then air-cooled to prepare alloy rods.
[0021] S4. The alloy rod is solution treated at 1100℃ for 2 hours, then aged at 900℃ for 4 hours, air-cooled to room temperature, and finally aged at 760℃ for 12 hours, and air-cooled to room temperature.
[0022] As described above and in any possible implementation, a further implementation is provided, wherein S1 includes:
[0023] S11. Add Ni, Co, Cr, Ti, W, Mo, Nb and Ta, which have high melting points, to the vacuum induction furnace to form an intermediate alloy;
[0024] S12. Add Al, C, B, Zr and Hf to the intermediate alloy and smelt to obtain a molten metal, then cast the molten metal into an alloy ingot.
[0025] Beneficial effects of the present invention
[0026] The high-strength, ductile, and easily machinable nickel-cobalt-based superalloy of the present invention comprises, by mass percentage: Co 18%–25%, Cr 11%–16%, Al 2.4%–3.4%, Ti 4.5%–6.5%, W 0.8%–2%, Mo 1.6%–3.2%, Ta 0.5%–1.5%, Nb 0%–1.5%, C 0.001%–0.1%, B 0.001%–0.05%, Zr 0.001%–0.1%, Hf 0–0.1%, with the balance being Ni. The present invention, through a rational element ratio, adjusts the alloying element distribution in the γ and γ′ phases. On the one hand, this allows the alloy to maintain a high γ′ phase volume fraction while possessing a large processing range; on the other hand, it adjusts the alloy stacking fault energy to fully utilize the strengthening effect of the interaction of surface defects. The combined effect of these two factors provides a solution for inventing a nickel-cobalt-based wrought superalloy that combines high strength, high plasticity, and easy processing, thereby offering a new solution for high-strength superalloys used in advanced equipment operating at temperatures of 750°C and above. Attached Figure Description
[0027] Figure 1 (a) is a SEM microstructure of the alloy of Example 1 of the present invention; (b) is an EBSD microstructure of the alloy of Example 1 of the present invention; and (c) is a tensile creep curve of the alloy of Example 1 of the present invention at 760℃ / 480MPa.
[0028] Figure 2 (a) is a TEM image of the deformed microstructure of the alloy of Example 2 of the present invention; (b) is a high-resolution atomic image of the deformed microstructure of the alloy of Example 2 of the present invention; and (c) is a tensile creep curve of the alloy of Example 2 of the present invention at 760℃ / 480MPa. Detailed Implementation
[0029] To better understand the technical solution of this invention, the content of this invention includes, but is not limited to, the specific embodiments described below. Similar technologies and methods should be considered within the scope of protection of this invention. To make the technical problems to be solved, the technical solutions, and advantages of this invention clearer, a detailed description will be provided below in conjunction with the accompanying drawings and specific embodiments.
[0030] It should be understood that the embodiments described in this invention are merely some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0031] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0032] This invention provides a high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy and its preparation method. The aim is to develop an alloy that exhibits high yield strength, large elongation after fracture, and good creep properties at intermediate temperatures, while possessing good plastic deformation forming ability at high temperatures. Furthermore, this superalloy exhibits a yield strength exceeding 1100 MPa at 750℃, an elongation after fracture exceeding 8%, a creep life exceeding 180 hours at 760℃@480 MPa, and a creep life exceeding 100 h at 1050℃. -2 s -1 When subjected to tensile strain at a certain strain rate, the elongation after fracture is above 1200%.
[0033] To achieve the above objectives, the present invention adopts the following technical solution:
[0034] High-strength, ductile, and easily machinable nickel-cobalt-based superalloys, comprising by mass percentage: Co 18%–25%, Cr 11%–16%, Al 2.4%–3.4%, Ti 4.5%–6.5%, W 0.8%–2%, Mo 1.6%–3.2%, Ta 0.5%–1.5%, Nb 0%–1.5%, C 0.001%–0.1%, B 0.001%–0.05%, Zr 0.001%–0.1%, Hf 0–0.1%, with the balance being Ni.
[0035] Preferably, the high-strength, ductile, and easily machinable nickel-cobalt-based superalloy comprises, by mass percentage: Co 21%–23%, Cr 12%–13%, Al 2.7%–3.1%, Ti 4.5%–6%, W 1.2%–1.6%, Mo 2.1%–2.6%, Ta 0%–1.2%, Nb 0%–1.2%, C 0.01%–0.04%, B 0.001%–0.03%, Zr 0.001%–0.03%, Hf 0–0.03%, with the balance being Ni.
[0036] Preferably, the high-temperature alloy comprises, by mass percentage: Co 20%–23%, Cr 12%–13.5%, Al 2.7%–3.2%, Ti 4.5%–6.5%, W 1.2%–1.8%, Mo 2%–2.6%, Ta 0%–1.5%, Nb 0%–1.5%, C 0.01%–0.05%, B 0.001%–0.04%, Zr 0.001%–0.04%, Hf 0–0.04%, with the balance being Ni.
[0037] The mass percentage ratio of Al to Ti is ≤0.6 to improve the mid-temperature strength of the alloy; the sum of the mass percentages of W and Mo is between 3% and 5% to ensure the solid solution strengthening effect of the alloy and improve the creep life of the alloy; the sum of the mass percentages of Nb and Ta is between 0% and 2% to reduce the stacking fault energy of the alloy, improve the yield strength of the alloy, and at the same time ensure the microstructure stability of the alloy.
[0038] The ratio of the mass percentage of Co to the mass percentage of W+Mo is ≥4 to control the solid solubility of refractory elements; the ratio of the mass percentage of Al to the mass percentage of Nb+Ta is ≥2 to ensure the contribution of Ni3Al to the relative strength and creep properties of the alloy.
[0039] Furthermore, the mass percentage of Co is between 20% and 24%, and the mass percentage ratio of Cr to Co is ≥0.5, in order to improve the alloy's resistance to oxidation and corrosion.
[0040] Furthermore, the sum of the mass percentages of W and Mo is between 3% and 5%, with W accounting for 1% to 2% and Mo accounting for 2% to 3%, thereby reducing the tendency of TCP harmful phases to precipitate while ensuring the solid solution strengthening effect.
[0041] Furthermore, the sum of the mass percentages of Al and Ti is 7% to 9%, thereby controlling the volume fraction of the alloy strengthening phase γ′ to be between 40% and 60%.
[0042] As an embodiment of the present invention, the present invention provides a method for preparing a high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy, comprising alloy smelting, extrusion deformation, and heat treatment processes, the steps of which are as follows:
[0043] (1) The alloy raw materials are added to a vacuum induction furnace for melting. The process is divided into two steps. First, elements with high melting points such as Ni, Co, Cr, Ti, W, Mo, Nb, and Ta are added and melted into an intermediate alloy. Then, easily volatile Al and trace elements C, B, and Zr are added and melted to control the loss of alloy elements. Finally, the molten metal is cast to obtain an alloy ingot.
[0044] (2) The alloy ingot is subjected to a step-by-step homogenization process. First, it is treated at 1050℃~1150℃ for 12h, and then at 1150℃~1200℃ for 16h. It is then air-cooled to room temperature. In this way, without causing initial melting, a portion of the primary γ′ phase is retained for pinning grain boundaries, while dendrite segregation is reduced, laying the foundation for the next step of deformation processing.
[0045] (3) The homogenized alloy is subjected to cladding extrusion at 1060℃~1090℃ with an extrusion ratio of 2.5~4. After extrusion, it is air-cooled to prepare an alloy rod. The alloy undergoes dynamic recrystallization during extrusion in this temperature range, and a fine-grained structure is obtained after extrusion.
[0046] (4) The alloy rod prepared by extrusion was solution treated at 1100℃ for 2h, then aged at 900℃ for 4h, air-cooled to room temperature, and finally aged at 760℃ for 12h, and air-cooled to room temperature, so that fine strengthening phase γ′ phase precipitates in the crystal.
[0047] The high-temperature alloy prepared according to the described method (smelting, encasing extrusion, solution aging) contains both pinned grain boundary γ′ phase and intragranular precipitation strengthening γ′ phase. The volume fraction of the intragranular strengthening phase is between 40% and 60%, allowing for a sufficient balance between the alloy's strength and plasticity. The alloy machined parts have a strength of 0.48–0.68T. m Temperature and 10 -4 ~10 -2 s -1 When plastic deformation is performed within the strain rate range, the low stacking fault energy characteristic results in the presence of both stacking faults and microtwins in the deformed alloy microstructure, with the microtwin thickness being less than 100 nm; among which, T m This is the melting point of the alloy.
[0048] The design principles for the role of alloying elements and their composition ranges in this invention are as follows:
[0049] Cobalt (Co) is the most important element in the alloy of this invention. On the one hand, the addition of Co can significantly reduce the stacking fault energy of the alloy's γ matrix, which is beneficial for promoting the a / 2... <110> The dislocations decompose into partial dislocations, which in turn form stacking faults and microtwins, promoting the transformation of stacking faults into microtwins and interacting with the γ′ phase to achieve a strengthening effect. On the other hand, the interaction between the added Co and Ni elements increases the volume fraction of the secondary γ′ phase, thereby improving the mechanical properties of the alloy. Therefore, the mass percentage of Co is 18%–25%, preferably 20%–23%.
[0050] Chromium (Cr): Cr is an important element for ensuring the oxidation and corrosion resistance of alloys. Due to its larger atomic radius than Ni and Co, it also has the effects of solid solution strengthening and reducing stacking fault energy. However, excessive addition of Cr can lead to the precipitation of harmful phases such as the σ phase, impairing the mechanical properties of the alloy. Therefore, the mass percentage of Cr is 11%–16%, preferably 12%–13.5%.
[0051] Aluminum (Al) is one of the main forming elements of the strengthening γ′ phase, primarily playing a role in precipitation strengthening and resistance to high-temperature oxidation. Adding Al can significantly improve the high-temperature mechanical properties of the alloy, but excessive Al content deteriorates the alloy's hot workability. Therefore, the mass percentage of Al is 2.4%–3.4%, preferably 2.7%–3.2%.
[0052] Titanium (Ti): Ti is one of the main forming elements of the strengthening γ′ phase and plays an important role in the mid-temperature strength of the alloy. Adding Ti can also increase the volume fraction and dissolution temperature of the γ′ strengthening phase, thereby improving the mechanical properties of the alloy. However, excessive Ti content can easily lead to the precipitation of the harmful η phase, impairing the alloy's mechanical properties. Therefore, the mass percentage of Ti is 4.5%–6.5%, preferably 4.5%–6.5%.
[0053] Tungsten (W) is a significant solid solution strengthening element that can simultaneously improve the strength of both the γ and γ′ phases. In nickel-cobalt based superalloys, it mainly enters the γ′ phase, controlling its coarsening rate and improving the alloy's creep resistance. However, excessive W content increases the tendency for the precipitation of the harmful μ phase, leading to a decrease in alloy performance. Furthermore, increased W content also increases the alloy's density, limiting its application range. Therefore, the mass percentage of W is 0.8%–2%, preferably 1.2%–1.8%.
[0054] Molybdenum (Mo) is a strong solid solution strengthening element that preferentially enters the γ matrix in nickel-cobalt-based superalloys to provide solid solution strengthening. Excessive Mo content can lead to the precipitation of the harmful σ phase, impairing the alloy's mechanical properties. Therefore, the mass percentage of Mo is 1.6%–3.2%, preferably 2%–2.6%.
[0055] Tantalum (Ta) is an essential element that must be added to the alloy of this invention. On one hand, Ta is a γ′ phase-forming element, which can increase the volume fraction of the γ′ strengthening phase. On the other hand, the addition of Ta can reduce the stacking fault energy of the alloy's γ matrix, making it easier for the alloy to form stacking faults and microtwins, which is a key guarantee for the alloy's strength at 750°C. However, excessively high Ta content may increase D0. 19 The tendency for harmful phases to precipitate impairs the mechanical properties of the alloy. Therefore, the mass percentage of Ta is 0.5% to 1.5%, preferably 0.5% to 1.5%.
[0056] Niobium (Nb) is a γ′ phase forming element and can also reduce the stacking fault energy of the alloy's γ matrix. However, excessively high Nb content can easily induce the formation of the δ-Ni3Nb phase. Therefore, the mass percentage of Nb is 0% to 1.5%, preferably 0% to 1.5%.
[0057] Carbon (C) is an important grain boundary strengthening element and also improves the casting properties of alloys. C segregates at grain boundaries to form MC, M6C, and M... 23 Carbides such as C6 can improve the mechanical properties of alloys. However, when the C content is too high, the continuous precipitation of carbides at grain boundaries will impair the mechanical properties of the alloy. Therefore, the mass percentage of C is 0.001% to 0.1%, preferably 0.01% to 0.05%.
[0058] Boron: Boron (B) segregates at grain boundaries, which can improve the grain boundary strength, hot deformation properties, and tensile plasticity of the alloy. However, when the boron content is too high, low-melting-point borides are easily formed between dendrites, making it more difficult to homogenize the alloy. Therefore, the mass percentage of boron is 0.001% to 0.05%, preferably 0.001% to 0.04%.
[0059] Zirconium: Zr segregates at grain boundaries, which can improve the plasticity and fatigue properties of the alloy. However, excessive Zr content can also increase the difficulty of alloy homogenization. Therefore, the mass percentage of Zr is 0.001% to 0.1%, preferably 0.001% to 0.04%.
[0060] Hafnium (Hf) segregates at grain boundaries, which can inhibit grain boundary slip and crack initiation, and improve the high-temperature creep strength and rupture life of the alloy. However, if the Hf content is too high, a brittle Hf-rich phase will be formed, leading to a decrease in the elongation after fracture of the alloy. Therefore, the mass percentage of Hf is 0–0.1%, preferably 0–0.04%.
[0061] The reasonable ratio of the above alloying elements is the guarantee that the high-strength, ductile, and easy-to-process nickel-cobalt-based superalloy of this invention achieves excellent room temperature and high temperature performance.
[0062] The present invention will be further illustrated below through specific embodiments:
[0063] Example 1
[0064] Example 1 describes the preparation of a high-strength, ductile, and easily machinable nickel-cobalt-based superalloy. The chemical composition of the superalloy, by mass percentage, is as follows: Co 22%, Cr 12.5%, Al 2.9%, Ti 5.5%, W 1.6%, Mo 2.4%, Ta 0.5%, Nb 0.5%, C 0.02%, B 0.02%, Zr 0.03%, Hf 0.01%, with the balance being Ni.
[0065] The preparation method of this high-temperature alloy is as follows:
[0066] 1) The alloy raw materials are added to a vacuum induction furnace for smelting. This process is divided into two steps. First, elements with high melting points such as Ni, Co, Cr, Ti, W, Mo, Nb, and Ta are added and smelted into an intermediate alloy. Then, easily volatile Al and trace elements such as C, B, Zr, and Hf are added and smelted. The molten metal is then cast into an alloy ingot.
[0067] 2) The alloy ingot is homogenized by first treating it at 1100℃ for 12 hours, then at 1175℃ for 16 hours, and then air-cooled to room temperature.
[0068] (3) The homogenized alloy was subjected to cladding extrusion at 1180℃ with an extrusion ratio of 3.5. After extrusion, the alloy rod was air-cooled to prepare the alloy rod.
[0069] 4) The extruded alloy rod is solution treated at 1100℃ for 2 hours, then aged at 900℃ for 4 hours, air-cooled to room temperature, and finally aged at 760℃ for 12 hours, and air-cooled to room temperature.
[0070] The high-temperature alloy microstructure photographs obtained according to this embodiment are as follows: Figure 1 As shown, (a) is the SEM microstructure of the alloy after heat treatment, which shows that the primary γ′ phase pinning the grain boundaries plays a role in controlling grain growth during heat treatment; at the same time, there is also a secondary γ′ phase precipitated within the grains, which plays a role in precipitation strengthening. (b) is the EBSD image of the grain structure of the alloy after heat treatment. The average grain size of the alloy is about 9 μm, which can play a significant role in grain refinement strengthening, thereby giving the alloy a high yield strength.
[0071] In this embodiment, the alloy is heated to 750°C at a rate of 10... -3 s -1 The strain rate tensile yield strength is 1110 MPa, the tensile strength is 1163 MPa, and the elongation after fracture is 9.0%.
[0072] The test results showed that the creep life of the alloy at 760℃@480MPa was 180h. Figure 1 As shown in (c).
[0073] Example 2
[0074] Example 2 describes the preparation of a high-strength, ductile, and easily machinable nickel-cobalt-based superalloy. The chemical composition of the superalloy, by mass percentage, is as follows: Co 22%, Cr 12.5%, Al 2.9%, Ti 5.5%, W 1.6%, Mo 2.4%, Ta 1%, C 0.02%, B 0.02%, Zr 0.03%, Hf 0.02%, with the balance being Ni.
[0075] The preparation method of this high-temperature alloy is as follows:
[0076] 1) The alloy raw materials are added to a vacuum induction furnace for smelting. This process is divided into two steps. First, elements with high melting points such as Ni, Co, Cr, Ti, W, Mo, Nb, and Ta are added and smelted into an intermediate alloy. Then, easily volatile Al and trace elements such as C, B, Zr, and Hf are added and smelted. The molten metal is then cast into an alloy ingot.
[0077] 2) The alloy ingots were homogenized by first treating them at 1175℃ for 12 hours, then at 1200℃ for 16 hours, and then air-cooled to room temperature.
[0078] (3) The homogenized alloy was subjected to cladding extrusion at 1180℃ with an extrusion ratio of 3.5. After extrusion, the alloy rod was air-cooled to prepare the alloy rod.
[0079] 4) The extruded alloy rod is solution treated at 1100℃ for 2 hours, then aged at 900℃ for 4 hours, air-cooled to room temperature, and finally aged at 760℃ for 12 hours, and air-cooled to room temperature.
[0080] A portion is cut from the heat-treated alloy bar to serve as a machined part, and then processed at 750°C with a 10°C feed rate. -3 s -1 Tensile tests were conducted at a strain rate of 10 at 1050℃. -2 s -1 Tensile tests were conducted at a strain rate of [value missing]. The microstructure of the alloy after tensioning is as follows: Figure 2 As shown, where Figure 2 In the middle (a), the bright-field phase containing stacking faults and microtwins is shown in the tensile microstructure of the alloy. The large number of parallel stacking faults and microtwins demonstrates the contribution of reducing stacking fault energy to increasing the stacking fault and microtwin density to the alloy's strength at 750°C. Figure 2 (b) is a high-resolution image of microtwins in the tensile structure of the alloy, which shows that microtwins can coordinate deformation by thickening, thereby improving the plasticity of the alloy.
[0081] The tests showed that the alloy had a yield strength of 1141 MPa, a tensile strength of 1218 MPa, and an elongation after fracture of 10.6% at 750℃; the elongation after fracture of the alloy at 1050℃ was 1240%, indicating that it has excellent strength, plasticity and hot working properties.
[0082] The test results showed that the creep life of the alloy at 760℃@480MPa was 183h. Figure 2 As shown in (c) in the figure.
[0083] The foregoing description illustrates and describes several preferred embodiments of the present invention. However, as previously stated, it should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the inventive concept described herein through the foregoing teachings or techniques or knowledge in related fields. Any modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.
Claims
1. A high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy, characterized in that, The composition by mass percentage includes: Co 20%~24%, Cr 12%~13.5%, Al 2.7%~3.2%, Ti 4.5%~6.5%, W 1.2%~1.8%, Mo 2%~2.6%, Ta 0.5%~1.5%, Nb 0%~1.5%, C 0.01%~0.05%, B 0.001%~0.04%, Zr 0.001%~0.04%, Hf The alloy contains 0.01~0.4% Al, with the balance being Ni. The mass percentage ratio of Al to Ti is ≤0.6; the sum of the mass percentages of W and Mo is 3%~5%; the sum of the mass percentages of Nb and Ta is 0%~2%; the mass percentage ratio of Co to W+Mo is ≥4; the mass percentage ratio of Al to Nb+Ta is ≥2; and the mass percentage ratio of Cr to Co is ≥0.
5. The high-temperature alloy contains both pinned grain boundary γ' phase and intragranular precipitation strengthening γ' phase, with the intragranular strengthening phase volume fraction between 40%~60%, ensuring a sufficient balance between alloy strength and plasticity. The alloy processed parts have a thickness of 0.48~0.68T. m Temperature and 10 -4 ~10 -2 s -1 When plastic deformation is performed within the strain rate range, the low stacking fault energy characteristic results in the presence of both stacking faults and microtwins in the deformed alloy microstructure, with the microtwin thickness being less than 100 nm; among which, T m The melting point of the alloy; the yield strength at 750℃ is above 1100MPa, and the elongation after fracture is above 8%; the creep life at 760℃@480MPa is above 180h; and the creep life at 1050℃ is above 100h. -2 s -1 When subjected to tensile strain at a certain strain rate, the elongation after fracture is above 1200%.
2. The alloy according to claim 1, characterized in that, The high-temperature alloy comprises, by mass percentage: Co 21%~23%, Cr 12%~13%, Al 2.7%~3.1%, Ti 4.5%~6%, W 1.2%~1.6%, Mo 2.1%~2.6%, Ta 0.5%~1.2%, Nb 0%~1.2%, C 0.01%~0.04%, B 0.001%~0.03%, Zr 0.001%~0.03%, Hf 0.01~0.03%, with the balance being Ni.
3. The alloy according to claim 1, characterized in that, The sum of the mass percentages of Al and Ti is 7% to 9%.
4. A method for preparing a high-strength, ductile, and easily machinable nickel-cobalt-based wrought superalloy, characterized in that, The method for preparing the alloy according to any one of claims 1-3 includes the following steps: S1. The raw materials are added to a vacuum induction furnace to melt alloy ingots; S2. The alloy ingot is homogenized by first treating it at 1050℃~1150℃ for 12 hours, then treating it at 1150℃~1200℃ for 16 hours, and then air-cooling it to room temperature. S3. The homogenized alloy is subjected to cladding extrusion at 1060℃~1090℃, and then air-cooled to prepare alloy rods. S4. The alloy rod is solution treated at 1100℃ for 2 hours, then aged at 900℃ for 4 hours, air-cooled to room temperature, and finally aged at 760℃ for 12 hours, and air-cooled to room temperature.
5. The preparation method according to claim 4, characterized in that, S1 includes: S11. Add Ni, Co, Cr, Ti, W, Mo, Nb and Ta, which have high melting points, to the vacuum induction furnace to form an intermediate alloy; S12. Add Al, C, B, Zr and Hf to the intermediate alloy and smelt to obtain a molten metal, then cast the molten metal into an alloy ingot.
Citation Information
Patent Citations
High-temperature alloys with low stacking fault energy, structural components and their applications
CN112981186B
Nickel-based heat-resistant superalloy
US9945019B2
High-temperature alloy with low stacking fault energy, structural part and application of high-temperature alloy
CN112981186A
800 DEG C-resistant high-toughness nickel-based wrought superalloy, preparation method thereof and turbine disc
CN119464840A
Nickel-based powder superalloy, preparation method thereof and turbine disc
CN119753437A
